International expert agenda in education: Key characteristics and problem areas - P. S. Sorokin; Yu. A. Vyatskaya (Obrazovanie i Nauka)
Introduction. This article presents an analysis of the global expert discourse in education prior to the Covid-2019 pandemic.Aim. The current research aims to analyse expert reports, regarding the theoretical foundations, articulated key trends, stakeholders and skills seen as educational outcomes.Methodology and research methods. The sample consists of 25 reports published in 2012–2020 by leading expert organisations (OECD, World Bank, etc.) devoted to the problems of education (school or higher education) and the relationship between education and the labour market. The main research method is critical discourse analysis.Results. Despite the dominance of the ideas of human capital in these reports, the relationship between “demand”, seen through the prism of global trends, and “supply” in the form of skills that education should provide, turns out to be problematic. Among the main stakeholders in education, managers and administration of educational institutions are emphasised in expert reports. Employers and learners are seen as rather passive players in the educational field. Physical health skills and agency skills are underestimated in global expert discourse despite their increasing relevance demonstrated by COVID-19 pandemic. These findings call for new approaches in global discussion about educational content and results in the context of global pandemic COVID-19.The scientific novelty of the research lies in the empirically grounded analysis of leading international expert discourse, about which there are many stereotypes, often without an evidence base.The practical significance of the study is in the identification of concrete problem areas of international expert discussion in education (at the time before the outbreak of the pandemic) that require strengthening, including on the basis of new research.